Pengaruh Transparansi Dan Akuntabilitas Laporan Keuangan Terhadap Kepercayaan Donatur Di Yayasan Sosial Keagamaan - Nikmahtul Maulidiyah; Darno Darno (Institut Ilmu Sosial dan Manajemen Stiami, 2019)
The Yadufa Cup Religious Social Foundation is a non-profit entity that is aware of its rights and obligations as well as its roles and responsibilities to Islam, the homeland and the nation. This foundation also has ZISWAH services (Zakat, Infaq, Shodaqoh, Endowments and Grants) which will later be distributed to Yadufa and empowered for social and community. This study aims to determine whether there is an influence of financial report transparency on donor trust in the Yadufa Cup of Religious Social Foundation. The research method uses quantitative research using the RLB test. This research produces 3 things: the first, that the transparency of financial statements does not significantly influence the trust of donors. Second, it shows that the accountability of financial statements has a significant effect on the trust of donors. Third, it shows that the transparency and accountability of financial statements simultaneously influences donor trust. Based on the RLB analysis, the transparency and accountability of financial statements can be a predictor of the trust of donors at the Yadufa Cup of Religious Social Foundation. The SEE value turns out to be smaller than the standard deviation value, so this regression model can be used as a prediction of the level of trust of donors in the future.